Export and import of Indian dairy products: An assessment - Jagruti Das and Ajmer Singh (Indian Journal of Dairy Science, 2022)
The economic policy reforms in India triggered in 1991 were reoriented towards liberalization and integration with the world economy and widened the market opportunities for the livestock sector. Sustained economic growth and rising incomes during the past two decades have been fuelling a rapid growth in the demand for livestock products. On the other side, apprehensions are being raised about the ability of Indian livestock farmers, a majority of whom are small and marginal, in taking the advantage of emerging opportunities, under the liberalized trade scenario. Also, non-tariff barriers like stringent Sanitary and Phyto-Sanitary (SPS) standards, technical barriers to trade (TBT), anti-dumping duties, countervailing duties, etc. are emerging as the major constraints in tapping the benefits of export potential of the livestock. Well-targeted livestock research and development programs can meet the multiple challenges Â (Birthal et.al, 2004).The trends in export and import of dairy products in India , their diversification and stability with reference to individual product categories have been studied in detail. This paper throws a light on the forte of international trade and its status quo and trends in the past years pertaining to Indian dairy sector.